Implementation of Font Change Application for SNS by Image Selection - Yui Tanaka; Takayuki Fujimoto (Journal of ICT, Design, Engineering and Technological Science, 2017)
This paper proposes a new function, which changes fonts by selecting visual expressions of emotions. We have used different fonts for emotional expressions when creating documents. We know that emotional expressiveness can be improved spectacularly by using different fonts. Therefore, we developed a front-end application with a font adjustment function for SNS, premised on using plain texts. If the user selects an illustration of a certain emotion that he or she wants to add to the texts, the “font” of the text will be changed into the one that fits the selected emotion. Normally, the images are selected by typing characters. However, this application can change the characters of the texts based on the selected images and realize more intuitive character expression. Today, when creating some documents, considering fonts is a usual practice. It is clear that fonts give texts emotional meanings. By using this application, the emotional meaning provided by the font can be added to the characters. In short, the characters become the texts that can reach another person more accurately. It is possible to express a wide variety of emotions, and more smooth communication by texts can be expected. We propose the app that the user can attach their emotion to the text by font change function. This app will be expected to give us smooth communication by texts.